Strategi Penerapan Etika Bisnis Sebagai Dasar Penguatan Keberlanjutan Usaha - Siswohadi Siswohadi; Moh. Rizal Muzaqi; Salva Nur Hamid; Achmad Nur Amin; Nur Ayu Hasanah (JURNAL RISET MANAJEMEN (JURMA), 2026)
Resilience and business sustainability in the era of global competition are no longer determined solely by product excellence or cost efficiency, but highly depend on the quality of relationships built by companies with all stakeholders. Many business organizations grow rapidly yet experience sudden collapse due to failure to maintain integrity and comply with ethical norms in their operations. This study aims to formulate business ethics implementation strategies as a fundamental foundation in strengthening long-term business sustainability. Through a descriptive qualitative approach based on literature study, the results show that applying moral values such as honesty, fairness, and social responsibility functions as an instrument to create trust, stability, and superior reputation. Ethical strategies integrated into management systems are proven effective in minimizing conflict risks, expanding cooperation access, and building competitive advantages that are difficult to replicate. It is concluded that business ethics is not merely a normative obligation, but a strategic investment that determines business survival and sustainable growth.